Ten-year institutional experience in nasopharyngeal carcinoma: a comprehensive retrospective analysis - Devi, Ningthoujam Dinita; Baidya, Kishalay; Mahawar, Rahul; Panmei, Ruby; Miachieo, Kekhrieu; Devi, Akoijam Sunita; Sobita Devi, Yumkhaibam (International Journal of Research in Medical Sciences, 2024)
Background: Nasopharyngeal carcinoma (NPC) is relatively rare worldwide but exhibits a higher prevalence in specific geographic regions, particularly Southeast Asia and the North-Eastern states of India. In this study, we present a comprehensive analysis of a decade’s worth of data involving 117 patients with NPC at the Regional Institute of Medical Sciences, Imphal, Manipur, India. Methods: We retrospectively reviewed data from 117 newly diagnosed NPC patients spanning from 2012 to 2022. Key demographic parameters such as age, gender, presenting symptoms, and disease stage were meticulously documented. Survival outcomes were assessed using Kaplan-Meier survival curves. Results: Our analysis encompassed 117 patients. The median age at presentation was 54 years. Undifferentiated carcinoma emerged as the predominant histological subtype. Notably, patients with type 1 keratinizing carcinoma, cranial nerve involvement, and advanced disease stages exhibited significantly poorer overall survival outcomes. Conclusions: This retrospective analysis of nasopharyngeal carcinoma in the North-Eastern region of India highlights the critical significance of implementing early detection and intervention strategies for NPC in this specific geographical area, with the potential to improve patient outcomes.